Student’s perception of hybrid team-based and case-based learning in undergraduate endodontics education - Lee, Yuetqi; Lin, Galvin Sim Siang; Mamat, Rosnani Binti; Noorani, Tahir Yusuf (Springer Nature, 2025)
Background: Limited studies have explored the use of the hybrid approach combining team-based learning (TBL) and case-based learning (CBL) in dental education. This study evaluates how students perceive the hybrid TBL-CBL approach to learning endodontics and determines whether gender and ethnicity impact students’ perceptions.